2021
DOI: 10.13057/biodiv/d220959
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics of Malesian Diospyros (Ebenaceae) based trnL-F spacer sequences

Abstract: Abstract. Wanda IF, Djuita NR, Chikmawati T. 2021. Molecular phylogenetics of Malesian Diospyros (Ebenaceae) based trnL-F spacer sequences. Biodiversitas 22: 4106-4114. Diospyros is a genus composed of potential species as an economic commodity with high diversity. However, there is limited information on the phylogenetic relationship of this genus in the Malesian region. This study aimed to provide information on the species diversity through a DNA barcoding approach and revealing the phylogenetic information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Meanwhile, the amplicons produced by trnL-F primers were also somewhat longer than the counterparts obtained in Diospyros spp. (Ebenaceae), showing 367 bp long trnL-F IGS sequences (Wanda et al 2021). After manual editing, the putative trnL-F IGS had 372 bp length, which was still longer than the sequences found in Diospyros spp.…”
Section: Resultsmentioning
confidence: 84%
“…Meanwhile, the amplicons produced by trnL-F primers were also somewhat longer than the counterparts obtained in Diospyros spp. (Ebenaceae), showing 367 bp long trnL-F IGS sequences (Wanda et al 2021). After manual editing, the putative trnL-F IGS had 372 bp length, which was still longer than the sequences found in Diospyros spp.…”
Section: Resultsmentioning
confidence: 84%
“…Diospyros (family: Ebenaceae) is an ecologically and economically important group of flowering plants, covering many species of ebonies and persimmons. Its members comprise more than 500 species worldwide, with most species found across the Indo-Pacific region (Wallnöfer 2001;Wanda et al 2021). Plant species belonging to this genus are mostly dioecious with separated male and female plants.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their economic and ecological importance, Diospyros conservation through botanic gardens is crucial to facilitate intensive studies on their biology and prospective sustainable uses. Such studies on Diospyros have been continuously carried out at the Indonesian Botanic Gardens to support the conservation of this genus (Rindyastuti 2021;Rindyastuti et al 2021;Wanda et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The trnL-trnF gene is widely used since the 1990s (D'yachenko et al 2015;Hartvig et al 2015;Koohdar and Sheidai 2022;Kipkiror et al 2023), and has shown successful application in plant molecular systematics in flowering plants (Chen et al 2013), such as Mangifera spp. (Fitmawati et al 2017), Laurus nobilis , Taxus (Liu et al 2011(Liu et al , 2018, Diospyros (Wanda et al 2021), and Ziziphora (Dündar and Tümen 2023). It also can be used to distinguish plant species, such as Pteridaceae (Chen et al 2013), Syzygium sp.…”
Section: Introductionmentioning
confidence: 99%